Desain kurikulum mikro sustainable development goals di sekolah menengah pertama - Annisa Fitri; Rudi Susilana (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2021)
The implementation of values of sustainable development is an important requirement to prepare future generations.Seeing these needs, it is necessary to design a micro curriculum on sustainable development values. Researchers analyzed the perceptions of 241 science teachers in West Java about the urgency of SD (Sustainable Development) indicators into content that students must learn. The topic of waste pollution and renewable energy are the chosen materials to be studied. Teacher's perception of the urgency of the material indicators can be said to be homogeneous. After that, the researcher made a content design for implementing this curriculum. Three validators who are experienced science teachers provide a constructive evaluation of the content and learning evaluation components.Learning evaluation is expected to be varied by including non-test components to achieve SD competence which emphasizes psychomotor and affective aspects.This curriculum content design already has goals that are in accordance with the expected sustainable development competencies, but the material content and evaluation components need further development.